A Finite Element Method with Perfectly Matched Absorbing Layers for the Wave Scattering by a Periodic Chiral Structure (Journal of Computational Mathematics, 2007)
Consider the diffraction of a time-harmonic wave incident upon a periodic chiral structure. The diffraction problem may be simplified to a two-dimensional one. In this paper, the diffraction problem is solved by a finite element method with perfectly matched absorbing layers (PMLs). We use the PML technique to truncate the unbounded domain to a bounded one which attenuates the outgoing waves in the PML region. Our computational experiments indicate that the proposed method is efficient, which is capable of dealing with complicated chiral grating structures.
Keywords: Chiral media; Perfectly matched layer; Grating optics.